Cyclooxygenase-2 Modulates Glycosaminoglycan Production in the Skin During Salt Overload - Agócs, Róbert; Pap, Domonkos; Sugár, Dániel; Tóth, Gábor; Turiák, Lilla; Veréb, Zoltán; Kemény, Lajos; Tulassay, Tivadar; Vannay, Ádám; Szabó, Attila J. (Frontiers in Physiology, 2020)
Sodium can accumulate in the skin tissue, sequestered by negatively charged glycosaminoglycans (GAG). During dietary salt overload, the amount and charge density of dermal GAG molecules – e.g. hyaluronic acid (HA) and chondroitin sulphate (CS) – increases, however the regulation of the process is unknown. Previously, it has been demonstrated, that the level of cyclooxygenase-2 (COX-2) activity and the content of prostaglandin E2 (PGE2) are elevated in the skin due to high-salt consumption. A link between the COX-2/PGE2 system and GAG synthesis was also suggested. We hypothesized that in dermal fibroblasts (DFs) high-sodium concentration activates the COX-2/PGE2 pathway and also, that PGE2 increases the production of HA. Our further aim was to demonstrate that the elevation of the GAG content is ceased by COX-2 inhibition in a salt overloaded animal model. For this, we investigated the mRNA expression of COX-2 and HA synthase 2 enzymes as well as the PGE2 and HA production of DFs by qRT-PCR and ELISA, respectively. The results showed that both high-sodium concentration and PGE2 treatment increases HA content of the media. Sodium excess activates the COX-2/PGE2 pathway in DFs, and COX-2 inhibition decreases the synthesis of HA. In the animal experiment, the HA- and CS disaccharide content in the skin of male Wistar rats was measured using HPLC-MS. In the skin of rats receiving high-salt diet, the content of both HA- and monosulphated CS disaccharides increased, whereas COX-2 inhibition blocked this overproduction. In conclusion, high-salt environment could induce GAG production of DFs in a COX-2/PGE2-dependent manner. Moreover, the COX-2 inhibition resulted in a decreased skin GAG content of the salt overloaded rats. These data revealed a new DF-mediated regulation of GAG synthesis in the skin during salt overload.